2012
DOI: 10.1155/2012/135708
|View full text |Cite
|
Sign up to set email alerts
|

An Analytic Analysis of the Diffusive-Heat-Flow Equation for Different Magnetic Field Profiles for a Single Magnetic Nanoparticle

Abstract: This study analytically analyzes the changes in the temperature profile of a homogenous and isotropic medium having the same thermal parameters as a muscular tissue, due to the heat released by a single magnetic nanoparticle (MNP) to its surroundings when subject to different magnetic field profiles. Exploring the temperature behavior of a heated MNP can be very useful predicting the temperature increment of it immediate surroundings. Therefore, selecting the most effective magnetic field profile (MFP) in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…S. aureus thermal inactivation occurred following a 3 minute AMF exposure using anti-SA MNPs despite a maximum measured ambient temperature of 43°C, which is an insufficient temperature to induce S. aureus thermal inactivation. Recently, Dana and Gannot 31 estimated that AMF-excited MNPs could generate a significant transient temperature increase within nanometers of each MNP surface, and this MNP focused heating could describe a mechanism of S. aureus thermal inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus thermal inactivation occurred following a 3 minute AMF exposure using anti-SA MNPs despite a maximum measured ambient temperature of 43°C, which is an insufficient temperature to induce S. aureus thermal inactivation. Recently, Dana and Gannot 31 estimated that AMF-excited MNPs could generate a significant transient temperature increase within nanometers of each MNP surface, and this MNP focused heating could describe a mechanism of S. aureus thermal inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Although magnetic nanoparticle hyperthermia can generate a rapid temperature increase at the surface of a single MNP 31 , a theoretical study also showed that overdosing presents the potential for disseminated tissue heating due to simultaneous heat dissipation from a large number of MNPs dispersed in a macroscopic region of tissue 32 . Therefore, proper dosing and customization of magnetic field exposure parameters are necessary to facilitate a targeted temperature rise, and prevent undue tissue damage to the surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…These marked efficiency Biofouling 1229 differences between both heating techniques can be ascribed to the higher local temperature that MH can generate at the surface of the magnetite nanoparticles, which provokes a harmful heat transfer to the bacterial cells. Dana and Gannot (2012) have reported that alternating magnetic field-excited MNPs might produce a major temporary temperature increase within nanometers of each MNP surface, which presumably makes the local temperature reached around each nanoparticle a lot higher than the macroscopic value measured within all the suspension. In this way, even when the overall measured temperature is not life-threatening, the local heat emitted by nanoparticles can be sufficient to kill bacterial cells.…”
Section: Discussionmentioning
confidence: 97%
“…In related research, we were also interested in an estimation of heat flow from magnetically excited nanoparticles. The detailed theoretical analysis can be read in this paper (Dana & Gannot, 2012). This can help us estimate how many nanoparticles per volume are needed, based on their SAR, to produce enough power output (thus temperature rise) to affect tumor viability, whether by heat only or as an adjuvant tool with chemotherapy or radiotherapy (Overgaard et al, 2009).…”
Section: Methodsmentioning
confidence: 99%